(untitled) - Pelikan, Jaroslav (New Haven, 1992)
Jaroslav Pelikan provides a unique perspective on the university today by reexamining it in light of John Henry Cardinal Newman’s 150-year old classic The Idea of a University and showing how Cardinal Newman’s ideas both illuminate and differ from current problems facing higher education. Pelikan begins by affirming the validity of Newman’s first principle: that knowledge must be an end in itself. He goes on to make the case for the inseparability of research and teaching on both intellectual and practical grounds, stressing the virtues—free inquiry, scholarly honesty, civility in discourse, toleration of diverse beliefs and values, and trust in rationality and public verifiability—that must be practiced and taught by the university. He discusses the business of the university—the advancement of knowledge through research, the extension and interpretation of knowledge through undergraduate and graduate teaching, the preservation of knowledge in libraries, museums, and galleries, and the diffusion of knowledge through scholarly publishing. And he argues that be performing these tasks, by developing closer ties with other schools at all levels, and by involving the community in lifelong education, the university will make its greatest contribution to society...
Keywords: Universities and colleges,Trường Đại học và Cao đẳng